The Standings of Tax Receivables in Bankruptcy Cases : A Study on Managing and Settling Assets - Sunarmi Sunarmi; Detania Sukarja; Tri Murti Lubis (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The state's privilege right to tax receivables in bankruptcy cases is regulated differently under various laws and court decisions in Indonesia. In general, tax receivables in bankruptcy have privilege position over other creditors, including secured creditors such as banks, mortgage holders, fiduciary guarantees and finance companies, preferential creditors and concurrent creditors. The creditor’s tax debt to the state should be paid first before any payment to other creditors. However, the Director General of Tax under the Ministry of Finance of the Republic of Indonesia often faces problems in claiming the payment as the Ministry claims for the payment are always rejected by the Court. Each of the existing legal rules and decisions provides different answers to this problem, resulting in legal uncertainties. This research is conducted using the normative juridical approach and supported by the empirical analysis. The data collection is conducted by document studies and supported by court decisions. This research aims to inquire and analyse the position of tax receivables in the distribution of bankruptcy estate of debtors among other creditors, the role of the curators, both state and private curators, in the bankruptcy estate distribution in order to find a legal solution to the aforementioned issue according to the normative legal provisions that apply.